PENERAPAN PROTOKOL KESEHATAN UNTUK MEWUJUDKAN GENERASI SEHAT KAMPUNG KB PADA ERA NEW NORMAL - Bintang Narpati; Kardinah Indrianna Meutia (Jurnal Abdimas Bina Bangsa, 2022)
Corona Virus (Covid-19) is a virus that can spread like an outbreak and be transmitted to others caused by the SARS-CoV2 virus (MLE, 2020). Some patients affected by this virus recover without having to go to the hospital because they are categorized as having mild to moderate respiratory problems. However, there are some other patients due to the infection of the Covid-19 virus who have to get treatment in the hospital because the patient has a severe respiratory problem that requires the treatment of a medical team. Common symptoms for Covid-19 sufferers are cough, fever, sore throat, shortness of breath, etc. (Singh & Singh, 2020). The average period of the incubation period of this virus is approximately 5-6 days. With the incubation period that takes a relatively long time, it can cause an increasing mortality rate due to the Covid-19 virus (Rusdiana, 2021). Patients who have Covid-19 disease can result in acute respiratory distress syndrome (ARDS), pneumonia (pneumonia) and failure of several organs. Patients at high risk are elderly and sufferers who have a history of medical diseases such as hypertension, diabetes, heart disease, chronic respiratory diseases or cancer. The spread of this Virus through the mouth or nose of an already infected person through droplets or small liquid particles when they cough, sneeze, speak, sing or breathe. Corona Virus Disease 2019 (Covid-19) by the World Health Organization (WHO) has been designated as a global outbreak ("Coronavirus Disease (COVID-19)," 2020). At the end of December 2019, the first time the Covid-19 Virus arose in Wuhan City, China. Johns Hopkins University provided data released in 2021 that there are total cases in the world regarding Covid-19 reaching 225,389,505 and death cases around 4,642,054. The government has taken efforts to prevent and overcome the COVID-19 virus (Aulia et al., 2021) in order to reduce the rate of spread of this virus to the territory of Indonesia. In this pegabdian activity to the community, invites the community, especially kampung KB, to always live a healthy life with the concept of "New Normal" or Adaptation to New Habits (Adriadi et al., 2021), namely activities while maintaining health protocols. In this new normal era, daily behavior or behaviors that in the new normal are different from normal activities before the pandemic or before (Nadilla & Zebua, 2020). The Covid-19 virus is not over yet and to prevent the spread of transmission, discipline is needed in implementing health protocols, namely 5 M (dr. Fadhli Rizal Makarim, 2021)